Emission taxes, firm relocation, and product differentiation - Laura Birg; Jan S. Voßwinkel (European Journal of Law and Economics, 2021)
This paper studies the effect of an emission tax on the relocation decision in a duopoly with vertical product differentiation. We establish the relationship between an exogenous product quality markup, relocation cost, and emission taxation in a two-country-setting for three cases: (a) an environmental tax set only by one country, (b) non-cooperative environmental taxation in both countries, and (c) coordinated environmental taxation. We show that a larger product quality markup and, thus, weaker competition can serve as a substitute for environmental policy as both reduce emissions. However, weaker competition makes firm relocation more likely, which results in emission shifting instead of emission reduction. The higher the product quality markup, the more likely it is that at least one firm relocates to the foreign country. Emission taxation in the foreign country changes location decisions: If also the foreign country applies an emission tax, at least one firm stays in the home country. If both governments set taxes non-cooperatively, the low-quality firm always stays in the home country. If both countries set taxes cooperatively, both firms are more likely to stay in the home country. However, relocation of the low-quality firm is a possible outcome under cooperative taxation.
Keywords: H23; F18; L13; Q58; 340; Relocation; Environmental policy; Vertical quality differences; Emission tax